2020
DOI: 10.1186/s12891-020-3068-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fractures of hand and forearm in whole-body CT for suspected polytrauma in intubated patients

Abstract: Background: The aim of this study was to evaluate the potential of whole-body CT for diagnosis of hand and forearm fractures in intubated patients with suspected polytrauma. Methods: We performed a retrospective analysis on data collected from two trauma centres in Germany, including demographics, ISS, clinical symptoms, depiction in whole-body CT, and time to diagnosis. Results: Out of 426 patients included in the study, 66 (15.5%) suffered a hand or forearm fracture. The total number of fractures was 132, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We found that fractures of hand are more often detected in patients in cases with full inclusion of the hand in the wholebody CT (WBCT). This was more often achieved by placing the hands on the abdomen [6]. The ISS did not have an influence on the number of late diagnoses in our sample [6].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We found that fractures of hand are more often detected in patients in cases with full inclusion of the hand in the wholebody CT (WBCT). This was more often achieved by placing the hands on the abdomen [6]. The ISS did not have an influence on the number of late diagnoses in our sample [6].…”
Section: Introductionmentioning
confidence: 66%
“…While there is no definition of 'missed', delayed', or 'late', we decided to use the term 'late diagnosis' for injuries that were detected 24 h after admission but during hospitalisation as they were eventually found [3][4][5][6]. Fractures of the upper extremity may be associated with reduced quality of life [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Injuries of the hand may be missed in 3.5 to 25% of patients with polytrauma [ 1 , 2 ]. While there is no definition of ‘missed’, delayed’, or ‘late’, we decided to use the term ‘late diagnosis’ for injuries that were detected 24 h after admission but during hospitalisation as they were eventually found [ 3 6 ]. Fractures of the upper extremity may be associated with reduced quality of life [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that fractures of hand are more often detected in patients in cases with full inclusion of the hand in the whole-body CT (WBCT). This was more often achieved by placing the hands on the abdomen [ 6 ]. The ISS did not have an influence on the number of late diagnoses in our sample [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation